1999
DOI: 10.2337/diacare.22.5.678
|View full text |Cite
|
Sign up to set email alerts
|

Amputation prevention by vascular surgery and podiatry collaboration in high-risk diabetic and nondiabetic patients. The Operation Desert Foot experience.

Abstract: A specialized clinic for prevention of lower-extremity amputation is described. Initial and contralateral amputation rates appear to be far lower in this population than in previously published reports for similar populations. Relative to patients without diabetes, patients with diabetes were more than seven times as likely to have a lower-extremity amputation. These data suggest that aggressive collaboration of vascular surgery and podiatry can be effective in preventing lower-extremity amputation in the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(69 citation statements)
references
References 0 publications
1
65
0
3
Order By: Relevance
“…History has demonstrated that comprehensive multidisciplinary foot care programs improve the quality of care and can reduce amputation rates by 36% to 86%. [1][2][3][4][5][6][7][8][9][10][11][12] Development of distal revascularization techniques to restore pulsatile blood flow to the foot has been a major advancement in limb salvage.…”
mentioning
confidence: 99%
“…History has demonstrated that comprehensive multidisciplinary foot care programs improve the quality of care and can reduce amputation rates by 36% to 86%. [1][2][3][4][5][6][7][8][9][10][11][12] Development of distal revascularization techniques to restore pulsatile blood flow to the foot has been a major advancement in limb salvage.…”
mentioning
confidence: 99%
“…6 Other researchers report that multidisciplinary podiatric medical and vascular surgery care reduced major amputations 82% and achieved limb salvage rates of 83% at 5 years. 17,18 Multidisciplinary teams involving a chronic-care model reduced amputations 47.4%, and an outpatient clinic team consisting of podiatric medicine, orthopedics, endocrinology, and nursing maintained amputation rates despite a fourfold increase in diabetic patients. 19 Podiatric physicians also aid in reducing the use of resources and costs.…”
Section: Discussionmentioning
confidence: 99%
“…Das Tragen diabetesadaptierter orthopädischer Maß-schuhe mit individuell gefertigten Einlagen ist die entscheidende druckent- In einer retrospektiven Studie eines interdisziplinär arbeitenden deutschen Diabeteszentrums konnte gezeigt werden, dass bei 79% der bereits von vorbehandelnden Einrichtungen zur Majoramputation "freigegebenen" Patienten mit neuropathisch-ischämischem DFS durch ein integriertes Therapiekonzept die hohe Amputation verhindert werden konnte [24]. Auch in auf die Therapie des DFS spezialisierten klinischen Einrichtungen variiert die Frequenz der Majoramputationen erheblich (1,7-15,5%) [1,14,28,29,40,54]. Ein direkter Vergleich dieser Daten ist aufgrund der unterschiedlichen Vorselektion in Richtung pAVK und Osteomyelitis und fehlender Subgruppenanalysen in der Regel nicht möglich.…”
Section: Sekundärprophylaxe -Bedeutung Von Vertikal Vernetzten Behandunclassified